Elucidating the role of angiogenesis-related genes in colorectal cancer: a multi-omics analysis - Wei, Hao-tang; Xie, Li-ye; Liu, Yong-gang; Deng, Ya; Chen, Feng; Lv, Feng; Tang, Li-ping; Hu, Bang-li (Frontiers in Oncology, 2024)
Background: Angiogenesis plays a pivotal role in colorectal cancer (CRC), yet its underlying mechanisms demand further exploration. This study aimed to elucidate the significance of angiogenesis-related genes (ARGs) in CRC through comprehensive multi-omics analysis.Methods: CRC patients were categorized according to ARGs expression to form angiogenesisrelated clusters (ARCs). We investigated the correlation between ARCs and patient survival, clinical features, consensus molecular subtypes (CMS), cancer stem cell (CSC) index, tumor microenvironment (TME), gene mutations, and response to immunotherapy. Utilizing three machine learning algorithms (LASSO, Xgboost, and Decision Tree), we screen key ARGs associated with ARCs, further validated in independent cohorts. A prognostic signature based on key ARGs was developed and analyzed at the scRNA-seq level. Validation of gene expression in external cohorts, clinical tissues, and blood samples was conducted via RT-PCR assay.Results: Two distinct ARC subtypes were identified, and were significantly associated with patient survival, clinical features, CMS, CSC index, and TME, but not with gene mutations.Four genes (S100A4, COL3A1, TIMP1, and APP) were identified as key ARCs, capable of distinguishing ARC subtypes. The prognostic signature based on these genes effectively stratified patients into high-or low-risk categories. scRNA-seq analysis showed these genes were predominantly expressed in immune cells rather than cancer cells. Validation in two external cohorts and through clinical samples confirmed significant expression differences between CRC and controls.Conclusions: This study identified two ARG subtypes in CRC and highlighted four key genes associated with these subtypes, offering new insights into personalized CRC treatment strategies.